Cycling talent assessment - Test protocol - Hutsebaut, P.; Brunet, K. (2002)
The Canadian Cycling Association (CCA) has developed a talent assessment test in cycling that aims at estimating in a summary manner the cyclists talent. In concrete terms, the test measures the time it takes to complete a virtual distance of 0.4 mile on a CompuTrainer with a flying start. The performance time obtained is used as an indicator of the anaerobic lactic capacity, an important performance factor in cycling. The test is brief and simple, so that we can easily give it to several people in the same session. This can be interesting for cycling promotion activities, for recruiting young people in a club or for selecting them for their involvement in competition initiation programs, be it mountain biking, cross-country, downhill, road or track cycling or BMX.